Anticorpos IgY policlonais: ferramentas auxiliares para o estudo in vitro de Toxoplasma gondii - Ferreira Júnior, Álvaro (2012)
Specific polyclonal antibodies obtained from egg yolk of the immunized chicken are named immunoglobulin Y (IgY). Although functionally related to mammal immunoglobulin G (IgG), IgY presents advantages, as follows: (i) elevated purified amounts of antibodies from one egg; (ii) the reduced of immunized animal number (iii) no interference with rheumatoid factor or mammal Complement proteins; (iv) binds only to chicken specific Fc fragment receptor. Polyclonal IgY antibodies could be employed as a primary or secondary reagent to investigate pathogen and host relationship, proteomic studies or infectious microorganisms biology. Toxoplasma gondii is a worldwide intracellular parasite which infects warm-blood hosts, including human. Toxoplasmosis causes fetal disorders in human and domestic animals. Tachyzoites and bradyzoites of T. gondii are stages related to host cell parasitism and also toxoplasmosis pathogeny. The specific IgG antibodies of mice are used to investigate virulence factors associated to T. gondii and evaluate mechanisms correlated to host immune response modulation by parasite antigens. However reduced amounts of specific IgG antibodies are obtained from a bled animal. Chickens and mice could have distinct antigenic proteins recognition profile even though using identical immunization protocols, probably this a consequence of phylogenetic distance between these two species. Specific polyclonal IgY were obtained from T. gondii soluble total antigens (STAg) immunized chickens at average of 4 mg/mL of pure yolk by a low cost and easy method. High avidity anti-STAg polyclonal IgY recognized distinct weight molecular antigenic proteins at second booster, and these antibodies were applied in standardized immunoassays with T. gondii. First, tissue cysts, parasitophorus vacuoles and also extracellular tachyzoites were detected in sections of chronically infected mice brain by a IgY-immunohistochemistry assay, complementally tachyzoites also were identified in a monolayer of infected HeLa cells by a IgY-immunocytochemistry assay, both methods used a anti-IgY FITC-conjugate secondary antibody. Additionally, STAg proteins two-dimensionally resolved were proved against T. gondii purified specific IgY and mice antiserum by a Western blot assay, the results demonstrated that egg yolk chicken antibodies identified acid antigens better than mice antisera. Finally, incubation of T. gondii tachyzoites with polyclonal anti-STAg IgY reduced intracellular parasitism in HeLa cells culture. In conclusion, polyclonal anti-STAg IgY antibodies present efficacy for application in immunoassays which investigate antigenic proteins candidates to diagnostic or vaccines and T. gondii biology.